Limited permissibility of ENL-R and Mv-1-Lu mink cell lines to SARS-CoV-2 - Le Bideau, Marion; Pires de Souza, Gabriel Augusto; Boschi, Celine; Baudoin, Jean-Pierre; Penant, Gwilherm; Jardot, Priscilla; Fenollar, Florence; Colson, Philippe; Lenk, Matthias; La Scola, Bernard (Frontiers in Microbiology, 2022)
The SARS-CoV-2 pandemic started in ending 2019 in Wuhan, China, highlighted the scenario of frequent cross-species transmission events. From the outbreak possibly initiated by viral spill-over into humans from an animal reservoir, now we face the human host moving globally while interact with domesticated and peridomestic animals. The emergency of a new virus into the ecosystem leads to selecting forces and species-specific adaptations. The adaptation of SARS-CoV-2 to other animals represents a risk to controlling the dissemination of this coronavirus and the emergence of new variants. Since 2020, several mink farms in Europe and the USA have had SARS-CoV-2 outbreaks with human-mink and mink-human transmission, where the mink-selected variants possibly hold evolutionary concerning advantages. Here we investigated the permissivity of mink-lung derived cells using two cell lines, Mv-1-Lu and ENL-R, against several lineages of SARS-CoV-2, including some classified as variants of concern. The viral release rate and the infectious titers indicate that these cells support infections by different SARS-CoV-2 lineages. The viral production occurs in the first few days after infection with the low viral release by these mink cells, which is often absent for the omicron variant for lung cells. The electron microscopy reveals that during the viral replication cycle, the endomembrane system of the mink-host cell undergoes typical changes while the viral particles are produced, especially in the first days of infection. Therefore, even if limited, mink-lung cells may represent a selecting source for SARS-CoV-2 variants, impacting their transmissibility and pathogenicity and making it difficult to control this new coronavirus.